2023
DOI: 10.1021/acs.jafc.3c02669
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Transcriptome and Metabolome Concerning Intramuscular Fat Content in Beijing Black Pigs

Xinhua Hou,
Run Zhang,
Man Yang
et al.

Abstract: To study the characteristics of genes and metabolites related to intramuscular fat (IMF) content with less influence by breed background and individual differences, the skeletal muscle samples from 40 Beijing black pigs with either high or low IMF content were used to perform transcriptome and metabolome analyses. About 99 genes (twofold-change) were differentially expressed. Up-regulated genes in the high IMF pigs were mainly related to fat metabolism. The key genes in charge of IMF deposition are ADIPOQ, CID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
0
0
Order By: Relevance
“…Therefore, we employed combined lipidomic and transcriptomic analyses to explore those intricate phenomena. Currently, research on the intrinsic characteristics about porcine IMF is limited to comparing skeletal muscles with varying IMF content , or studying the in vitro differentiation of isolated unmature IMAs. , One limitation of comparing skeletal muscles is that muscle can influence the IMF transcriptome, while in vitro studies might not fully replicate in vivo conditions. Our analysis, involving dissection of porcine IMF for further study, showed that IMF is richer in unsaturated fatty acids and shows higher gene expression for unsaturated fatty acid synthesis compared to SCF, as previous findings .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we employed combined lipidomic and transcriptomic analyses to explore those intricate phenomena. Currently, research on the intrinsic characteristics about porcine IMF is limited to comparing skeletal muscles with varying IMF content , or studying the in vitro differentiation of isolated unmature IMAs. , One limitation of comparing skeletal muscles is that muscle can influence the IMF transcriptome, while in vitro studies might not fully replicate in vivo conditions. Our analysis, involving dissection of porcine IMF for further study, showed that IMF is richer in unsaturated fatty acids and shows higher gene expression for unsaturated fatty acid synthesis compared to SCF, as previous findings .…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the expression patterns of DEGs related to FA synthesis, such as ACACA , ACSF3 , OXSM , CBR4 , and HSD17B8 , between Mashen pigs and Large White pigs showed that IMF accumulation occurred between 90 and 180 days [ 49 ]. The key genes that regulate IMF deposition are ADIPOQ , CIDEC , CYP4B1 , DGAT2 , LEP , OPRL1 , PLIN1 , SCD and THRSP [ 50 ]. The GPAT1 , AGPAT1 , AGPAT2 , LIPIN1 , and DGAT genes are related to TG biosynthesis [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the meat yield, there is an increasing demand for high-quality meat. 1 Intramuscular fat (IMF) content is an important indicator for evaluating beef quality, closely related to the flavor, juiciness, tenderness, and nutritional value of beef. 2 Additionally, the abundance of polyunsaturated fatty acids (PUFAs) in IMF is more beneficial to cardiovascular health and reduces the risk of fat metabolism-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement in living standards, beef has become one of the primary sources of meat for humans. In addition to the meat yield, there is an increasing demand for high‐quality meat 1 . Intramuscular fat (IMF) content is an important indicator for evaluating beef quality, closely related to the flavor, juiciness, tenderness, and nutritional value of beef 2 .…”
Section: Introductionmentioning
confidence: 99%